2017
DOI: 10.1167/tvst.6.4.11
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Variability of Perimetric Global Indices from Eyes with Progressive Glaucoma by Censoring Unreliable Sensitivity Data

Abstract: PurposeRecent evidence suggests that increasing perimetric contrast all the way to 0 dB may not be clinically useful. This study examines whether raising the floor for point-wise sensitivities affects the ability of global indices to detect change.MethodsLongitudinal data from eyes with progressive glaucoma were used. Point-wise sensitivities were censored at various cutoffs (12–19 dB). At each cutoff, mean deviations (MD) were recalculated using censored sensitivities, called censored mean deviation (CMD). Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 16 publications
(29 reference statements)
1
15
2
Order By: Relevance
“…It could be argued that improvements in testeretest variability in the upper range of sensitivity values could be more clinically relevant for progression detection. [24][25][26][27][28][29] However, this is speculation because only analysis of long-term follow-up of glaucoma subjects with the CMP will allow the assessment of the real effect of such reduction in variability on earlier diagnosis of progression. Additionally, Wyatt et al 30 identified gaze instability as a possible source of variability at the edges of scotomata, and tracking might help reduce this effect.…”
Section: Discussionmentioning
confidence: 99%
“…It could be argued that improvements in testeretest variability in the upper range of sensitivity values could be more clinically relevant for progression detection. [24][25][26][27][28][29] However, this is speculation because only analysis of long-term follow-up of glaucoma subjects with the CMP will allow the assessment of the real effect of such reduction in variability on earlier diagnosis of progression. Additionally, Wyatt et al 30 identified gaze instability as a possible source of variability at the edges of scotomata, and tracking might help reduce this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Higher variance at locations with greater defect depth has been demonstrated by a number of other studies, 54,55 and there have also been suggestions for the censoring of perimetric data below certain sensitivity levels (15-19 dB). 31,56 When we censored our data below 19 dB, there was no difference in the slope values or goodness of fit, suggesting that moderate strength of correlation was not related to high variance at low sensitivities but rather was likely driven by algorithm differences.…”
Section: Are the Sita Algorithms Interchangeable?mentioning
confidence: 97%
“…26,27 However, the implementation of recommendations for increased frequency of testing has been challenging, with issues of timing and availability of resources being cited as barriers, despite long-term cost savings. 28 Alternative approaches, such as the use of previous sensitivity information, 29 adaptation to regions of interest, such as scotomata, 30 censoring of unreliable test points to reduce the number of stimulus presentations, 31 and the use of structural information for targeting specific regions of the visual field 32,33 remain theoretical at present and have not yet been widely implemented in practice.…”
mentioning
confidence: 99%
“…We do not fully threshold these locations, consistent with recent evidence that censoring data in this range does not alter the ability to detect progression in existing visual field datasets, determined using either global indices or on a pointwise basis. 21 , 22 We demonstrate that this new approach allows more complete visualization of the spatial nature of progressing visual field loss in glaucoma, without sacrificing specificity, and with an improvement in test time.…”
Section: Introductionmentioning
confidence: 86%
“…Note that the cutoff value of 16 dB is somewhat arbitrary, and perhaps even conservative as there is some evidence that using any values up to 19 dB might be appropriate. 18 , 21 , 22 …”
Section: Methodsmentioning
confidence: 99%